Content validity by expert judgment of an instrument to measure knowledge, attitudes and practices about salt consumption in the peruvian population: Validez de contenido por juicio de expertos de un instrumento para medir conocimientos, actitudes y prácticas sobre el consumo de sal en la población peruana - Torres-Malca, Jenny R. (2022)
Introduction: Given the high consumption of salt in the population, the need arises to have a validated tool that measures the knowledge, attitudes and practices of salt consumption (CAP-salt).  Objective: To validate the questionnaire on CAP-salt.  Methods: Psychometric study of content validity through expert judgment. A total of 5 physicians from different specialties were counted. To calculate the degree of agreement between the expert judges, Aiken's V was used. As a decision criterion to keep an item, a value ≥ 0.7 was considered.  Results: In relation to clarity, V values greater than 0.80 were presented, in addition to a variation coefficient of less than 25%, therefore, none of the items was eliminated. Regarding coherence, they presented a coefficient of variation above 20% and V values greater than 0.71, confirming the decision not to exclude any of them. Regarding the relevance of the items, V values higher than 0.90 were also evidenced and neither did any of them present a value below the critical one.  Conclusions: The questionnaire has presented sufficient evidence of content validity in terms of clarity, coherence and relevance of the items through the aforementioned analyses. For this reason, it should be used to quantify the KAP of different population groups in the country.